Structures of rational behavior in economics - Susanne Fuchs-Seliger (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
Describing individual behavior, we will be concerned with an axiom system, which can be interpreted by Shephard's distance function. Based on this function, one can discover the individual's preference relation, from which the individual's demand function can be derived. We will realize that the axiom system describes rational behavior, satisfying the Strong Axiom of Revealed Preference. The axiom system presented in this article is closely related to a former one describing consumer behavior by income compensation functions. These different approaches will help to illuminate choice behavior from different points of view. We will also see that the axiom system presented in this article can be interpreted by the economic quantity index in welfare theory and by distance functions in producer theory.
Keywords: D71; C78; 330; Economic Models; Demand Functions; Distance Functions; Rationality; Producer Theory; Welfare Theory